Distribution and determinants of young child feeding practices in the East African region: demographic health survey data analysis from 2008-2011. - Gewa, Constance A.; Leslie, Timothy F. (Journal of Health, Population & Nutrition, 2015)
We utilized the most recent Demographic Health Survey data to explore the distribution of feeding practices and examine relationships between complementary feeding and socio-demographic and health behaviour indicators in Kenya, Uganda and Tanzania. We based our analysis on complementary dietary diversity scores calculated for children 6-23 months old. Geographically, Kenya displayed clear division of children's diet diversity scores across its regions, unlike Uganda and Tanzania. Less than 40% of the children's meal frequencies in Uganda and Tanzania had met the minimum daily recommended levels. Only 30-40% of children in Kenya, Tanzania and Uganda had consumed diets with adequate diversity. Children's age, breastfeeding status, mother's education level and working status, household wealth index, prenatal care visits, receiving vitamin A supplements, using modern contraceptives and meal frequencies were significantly associated with adequate complementary food diversity in at least one of the three countries included in the current analyses. These analyses contribute to a better understanding and targeting of infant and young child feeding within the East African region.